Fluxo hídrico subterrâneo: modelagem computacional e calibração iterativa dos parâmetros hidrodinâmicos - Leal Júnior, Carlos Roberto Moura (2007)
The current work presents a computer simulation of groundwater flow in the Cariri Valley, which is located in the State of Ceará. The cities of Barbalha and Missão Velha are located inside this area. In order to perform the computer modeling the software Processing MODFLOW Pro was used. It was used both permanent and time dependent situations. Also both rainy and dry seasons periods we simulated. Among the results, it is show the variation of the groundwater levels and the direction of the flow. As a part of the work, a computer code, using DELPHI 5.0, was developed in order to implement the calibration of hydrogeologic parameters, such as hydraulic conductivity. This code is actually an interface between MODLFOW and the Alternate Hydraulic Gradient Method. This interface uses input date measured groundwater levels and it is on iterative method. Although, in the area of study this method could not reach satisfactory calibration results since accuracy of know groundwater levels and well discharge, as well as topographic contours were poor, the method seem to be valuable.